DISCOURSE MARKERS AS A LINGUISTIC TOOL FOR EFFECTIVE COMMUNICATION - Shakhnoza Abdurashitovna Abdurakhimova (Bright Mind Publishing, 2025)
Discourse markers (DMs) are crucial elements in both spoken and written communication, offering structure, clarity, and coherence to discourse. They help facilitate interactions, indicate shifts in topics, and ensure the smooth flow of conversations. Though they are not part of the core propositional content, DMs play an integral role in organizing ideas, expressing attitudes, and ensuring the speaker’s intentions are understood by the audience. This paper provides an in-depth analysis of discourse markers, their types, and their functions in communication. It explores their role in the acquisition of pragmatic competence, particularly for second language learners, and discusses the pedagogical implications of teaching these linguistic tools in language education. Through a review of existing literature and practical examples, the study highlights the importance of discourse markers in enhancing communication efficiency, language fluency, and interactional competence. The findings suggest that discourse markers are vital for effective communication and should be explicitly taught to language learners to enhance their practical language skills.
Keywords: Discourse markers, communication strategies, effective communication, pragmatics, cohesion and coherence, language functions, language teaching.